Assessment of the safety and efficacy of intravenous versus topical tranexamic acid in patients undergoing primary total hip and knee arthroplasty surgeries with respect to decreasing peri-operative blood loss and blood transfusion rates: a prospective and comparative study - Garg, Rohit N.; Dubey, Rakesh; Kundu, Soutrik; Gupta, Dinesh; Vaje, Shweta Sonu (International Journal of Research in Orthopaedics, 2024)
Background: Synthetic antifibrinolytic agent like tranexamic acid has been increasingly used in Arthroplasty surgeries to decrease the peri-operative blood loss. The current study was undertaken to compare the efficacy between the intravenous and Topical route of TXA in deceasing the blood loss and transfusion rate in patients undergoing primary total hip and knee arthroplasty (THR and TKR) surgeries. Methods: A total of 120 patients were enrolled in the study with 60 each undergoing THR and TKR surgeries with 30 each given TXA in IV and Topical routes. Outcomes were assessed in terms of mean 24 hours drain output, mean blood loss, mean drop in hemoglobin blood transfusion rate. Results: The mean drain output was more in the IV group in both THR and TKR patients (p>0.05). The mean blood loss was more in the Topical group in both THR and TKR patients (p>0.05). The mean drop in hemoglobin was more in the Topical group, with the difference being significant in the THR patients (p<0.05) and being insignificant in TKR patients (p>0.05). In IV group 9 patients (15%) and in Topical group 25 patients (41.67%) needed blood transfusions, the difference being statistically significant. Conclusions: Both IV and Topical routes of TXA are equally effective in decreasing the peri-operative blood loss and transfusion rates in patients undergoing primary arthroplasty surgeries, with IV route having slightly upper hand as compared to the Topical route.